Strategi Dinas Perikanan Kota Batam Dalam Mengoptimalisasi Kesejahteraan Masyarakat Nelayan: Indonesia - Riko Riyanda (Prodi Ilmu Administrasi Negara, 2018)
Geographically, ​​Batam is a group of islands which is very potential to build a maritime industry. Therefore, marine and fisheries sector arepromising sector in Batam. Data from BPS Batam and KP2K office showed the number of fishery production in Batam has increased since 2011 until 2015. This is also followed by the increasing of household fisheries (RTP) numbers, both marine catch and aquaculture fisheries. The purpose of this study is to describe and analyze the strategy of marine office, fishery, agriculture, and forestry office in Batamt optimize the prosperity of fishermen community. This research isa descriptive qualitative. Technique of collecting data was done by interview, observation and documentation. Based on data of Batam fishery office, fisheries,fishing cultivation,and household fisheries (RTP) increase every year. The prosperity strategies implemented by Batam fisheryoffice are: increasing fleet, modernization and motorization, conducting servicestoBatamfishermen and forum of microfinance institutions fishermen (LKMN) Bina Batam Madanias a media of fisherman prosperity. The obstacles faced by fishermen in Batam to achieve fisherman's prosperity are: fisherman facilities in Batamare still low, fish habitat in Batamdisturbed,and fisherman fleetis still low. However, strategic achievement of Batamfisheryoffice is quite effective in optimizing the fishermen prosperity in Batam.